SOCIO-CULTURAL AND ECONOMIC FACTORS AS DETERMINANTS OF PARTICIPATION OF FEMALES IN PART-TIME NCE PROGRAMMES IN SOUTH-WESTERN NIGERIA (2016)
The scraping of the Teachers Grade II certificate programme places great responsibilities on Nigerian Colleges of Education (COEs) in providing manpower with the minimum entry qualification to enter into the teaching profession in the country. The increasing demands for the Nigeria Certificate of Education (NCE) have forced COEs to establish part-time programmes with flexible admission criteria. Despite this, there exists low participation of women in these programmes; a situation partly attributed to the dominance of socio-cultural and economic factors. Although, studies exist on students’ participation in part-time NCE programmes, none has specifically focused on how socio-cultural and economic factors determine female participation in the programme. This study, therefore, investigated socio-cultural and economic factors as determinants of participation of female students in part-time NCE programmes in South-Western Nigeria. The descriptive survey research design was adopted. The multi-stage random sampling procedure was used in selecting 1024 female NCE students in Cohorts 1 – 4 in the School of Education across four centres each from three selected COEs. Data were collected using Female Participation Questionnaire with five sub-scales: Social Factors Scale (r = 0.81), Cultural Factors Scale (r = 0.93), Economic Factors Scale (r = 0.74), Participation Scale (r = 0.69) and Females Academic Performance Scale (r = 0.86). This was complemented with 12 sessions of Focus Group Discussions (FGDs) with selected female part-time NCE learners. Data were analysed using descriptive statistics, multiple regression and content analysis. Socio-cultural and economic factors significantly correlated with participation of female students in part-time NCE programmes (F (3, 1021) = 146.25, R2 = 0.50; p < 0.05); with relative contributions as ranked: economic factors (β = 0.52), social factors (β = 0.20) and cultural factors (β = 0.30). Social factors contributions in order of magnitude were parents encouragement (β = 0.89), parental level of education (β = 0.84), peers’ influence (β = 0.81), family background (β = 0.73), availability of female role models (β = 0.70), spouse level of education (β = 0.27), spouse’s encouragement (β = 0.11). Similarly, cultural factors’ contributions were: submissiveness to parental instructions (β = 0. 86), gender identity/labelling (β = 0.69), house responsibilities/chores (β = 0.20), spouse instructions (β = 0.14), practice of female seclusion (β = 0.10), early marriage (β = 0.09). Also, relative contributions of economic factors were: financial support (β = 0.51), parental occupation (β = 0.42), spouse occupation (β = 0.35) and cost of programme (β = 0.23). FGD revealed that marriage is the bane of their schooling. However, the motivating impetus for female participation in the programmes are the encouragement from parents, peers, role models and availability of financial supports. Parental background, encouragement, level of education, peers’ influence, availability of female role models, and availability of financial support were potent factors in enhancing participation of females in part-time Nigerian Certificate of Education programme. Therefore, there is the need for less culture-consciousness and spousal sensitization as well as reduction in cost of schooling to encourage participation of females in part-time Nigerian Certificate of Education programmes. Key words: Females’ participation, Part-time NCE programme, Socio-cultural and economic factors, Nigerian Colleges of Education Word count: 498